Platelet and plasma bioactive scaffolds for stem cell differentiation: What are we missing? - Moroz, Andrei [UNESP] (2014)
Univ Estadual Paulista, UNESP, Cell Engn Lab, Ctr Blood Transfus,Botucatu Med Sch, BR-18618970 Botucatu, SP, Brazil